Invasive central venous monitoring during hepatic resection: unnecessary for most patients. Issue 12 (December 2020) - O'Connor, David C.; Seier, Kenneth; Gonen, Mithat; McCormick, Patrick J.; Correa-Gallego, Camilo; Parker, Benjamin; Weiser, Emily; Balachandran, Vinod P.; Dematteo, Ronald P.; D'Angelica, Michael; Kingham, Peter T.; Allen, Peter J.; et al.
Abstract: Background: Low central venous pressure (LCVP) anesthesia reduces blood loss during hepatic resection and historically has required a central venous catheter (CVC) for intra-operative monitoring. The aim of this study was to assess the effect of an evolution of practice to CVP monitoring without CVC on the perioperative outcomes after liver resection. Methods: A retrospective study of partial hepatectomy patients from 2007 to 2016 who were over 18 years of age was performed. Results: Of 3903 patients having partial hepatectomy, 2445 (62%) met inclusion criteria, and 404 (16%) had a CVC. Overall morbidity (33% non-CVC vs 38% CVC P  = 0.076), major morbidity (16% vs 20% P  = 0.067), and infective complications (superficial wound infection) 3% vs 4% P  = 0.429; deep wound infection (5% vs 6% P  = 0.720) did not differ between the two groups. In multivariate analysis, superficial wound infection, deep wound infection, and major complications were not associated with the presence of a CVC. All-cause mortality at 90 days was associated with CVC presence (OR 3.45, CI 1.74–6.85, P  = 0.001) and age (OR 1.05, CI 1.02–1.08, P  < 0.001). Conclusion: Since the adoption of non-invasive CVP monitoring, there has been no increase in adverse peri-operative outcomes.